2017
DOI: 10.1002/pnp.482
|View full text |Cite
|
Sign up to set email alerts
|

Association between antipsychotics and adverse outcomes in dementia

Abstract: Prolonged use of antipsychotics continues to be a controversial subject area, especially in the older adult population due to age‐related changes in pharmacokinetic and pharmacodynamics parameters. Best practice guidelines recommends that they should be used at their lowest dosage for no longer than 6–12 weeks. Here, the authors discuss the prevalence of antipsychotic use to treat the behavioural and psychological symptoms of dementia in the older adult population and the dilemma it poses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Most of the results from the SUCRA ranking are congruent with published observational studies. For example, previous reports corroborate ranking quetiapine as the safest and risperidone as the least safe based on EPSs . Quetiapine was ranked as most likely to cause somnolence or sedation, which might explain why it is commonly used as a sedative-hypnotic in patients with dementia .…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Most of the results from the SUCRA ranking are congruent with published observational studies. For example, previous reports corroborate ranking quetiapine as the safest and risperidone as the least safe based on EPSs . Quetiapine was ranked as most likely to cause somnolence or sedation, which might explain why it is commonly used as a sedative-hypnotic in patients with dementia .…”
Section: Discussionmentioning
confidence: 66%
“…For example, previous reports corroborate ranking quetiapine as the safest and risperidone as the least safe based on EPSs. 65 , 66 Quetiapine was ranked as most likely to cause somnolence or sedation, which might explain why it is commonly used as a sedative-hypnotic in patients with dementia. 67 The ranking results for somnolence or sedation are similar to those of death and may be explained by the fact that excessive sedation or sleep is associated with infection, including pneumonia, which could ultimately lead to death.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the settings that received a psychotropic medication citation had an MC endorsement. This is expected, given higher psychotropic medication use among individuals with an ADRD diagnosis (Bangash et al, 2017;Mueller et al, 2021). A seven-state study of 250 AL/RC communities prescribing and administration of PRN psychotropic medications found that prescribing was higher among residents with a dementia diagnosis and in settings that were larger and had more dementia care beds (Carder et al, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…A significant share of assisted living/residential care (AL/RC) settings residents have Alzheimer’s disease or related dementia (ADRD) (42%), and an estimated 26–90% have cognitive impairment (Sengupta et al, 2022; Zimmerman et al, 2014). Psychotropic medication used to manage symptoms and behaviors associated with ADRD, including AL/RC residents (Maust et al, 2018; Thomas et al, 2021), presents a significant health policy concern because of their associations with adverse events (e.g., falls, mortality) and care provision implications (Bangash et al, 2017; Beeber et al, 2021; Crystal et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Partial tolerance develops with ongoing use, although this develops slowly. An increased risk of falls and hip fractures still occurs in chronic users of sedatives, increased risk also seen with patients using tricyclic antidepressants and antipsychotic medications …”
Section: Adverse Effects Of Medications Commonly Used For Sleep Disormentioning
confidence: 99%